FGF21 is a biomarker for mitochondrial translation and mtDNA maintenance disorders. (29th November 2016) - Lehtonen, Jenni M.; Forsström, Saara; Bottani, Emanuela; Viscomi, Carlo; Baris, Olivier R.; Isoniemi, Helena; Höckerstedt, Krister; Österlund, Pia; Hurme, Mikko; Jylhävä, Juulia; Leppä, Sirpa; Markkula, Ritva; et al.
Abstract : Objective: To validate new mitochondrial myopathy serum biomarkers for diagnostic use. Methods: We analyzed serum FGF21 (S-FGF21) and GDF15 from patients with (1) mitochondrial diseases and (2) nonmitochondrial disorders partially overlapping with mitochondrial disorder phenotypes. We (3) did a meta-analysis of S-FGF21 in mitochondrial disease and (4) analyzed S-Fgf21 and skeletal muscle Fgf21 expression in 6 mouse models with different muscle-manifesting mitochondrial dysfunctions. Results: We report that S-FGF21 consistently increases in primary mitochondrial myopathy, especially in patients with mitochondrial translation defects or mitochondrial DNA (mtDNA) deletions (675 and 347 pg/mL, respectively; controls: 66 pg/mL, p < 0.0001 for both). This is corroborated in mice (mtDNA deletions 1, 163 vs 379 pg/mL, p < 0.0001). However, patients and mice with structural respiratory chain subunit or assembly factor defects showed low induction (human 335 pg/mL, p < 0.05; mice 335 pg/mL, not significant). Overall specificities of FGF21 and GDF15 to find patients with mitochondrial myopathy were 89.3% vs 86.4%, and sensitivities 67.3% and 76.0%, respectively. However, GDF15 was increased also in a wide range of nonmitochondrial conditions. Conclusions: S-FGF21 is a specific biomarker for muscle-manifesting defects of mitochondrial translation, including mitochondrial transfer-RNA mutations and primary and secondary mtDNA deletions, the most common causes of mitochondrial disease. However, normal S-FGF21 does not exclude structural respiratory chain complex or assembly factor defects, important to acknowledge in diagnostics. Classification of evidence: This study provides Class III evidence that elevated S-FGF21 accurately distinguishes patients with mitochondrial myopathies from patients with other conditions, and FGF21 and GDF15 mitochondrial myopathy from other myopathies.